Formação de professores formadores: concepções e práticas em disciplinas da área de matemática do curso de pedagogia - Jesus, Ana Cristina Gomes de (2015)
In this research we have proposed to analyze the pedagogical practice of two teachers forming the discipline of mathematics area of the Pedagogy course of two Goiás State University, investigating the possible consequences of their training trajectories and their conceptions of mathematics and its teaching in educational performance. The methodological approach is a qualitative approach, making use of the Case Study method, with multiple cases, which was divided into two phases. In the first one documentary research was made to bibliographic lifting and data. In the second phase the observation of teaching practice of teacher educators, using as collection instrument the field diary and later one semi-structured interviews with the participants. To systematize and analyze the collected data used as the theoretical the French Discourse Analysis and authors as: Tardif, Mizukami, Orlandi, Vila and Callejo, Rose, Curi, Manfredo, Coracini, Pimenta, Anastasiou, Yin, among others. The results in this research signaled that the formative trajectory, in which the faculty knowledge are built, ensures influences in the performance of the participants forming teachers as well as the marks left by his former teaches. The concepts and held by them about mathematics and its teaching is presented and multifaceted that admits a dialogue with the educational practice developed in the gap between specific and pedagogical knowledge.